1
$\begingroup$

Given that $P(A\cup B)=P(A)+P(B)-P(A\cap B) $

How to show that $P(A\cap B)\geq P(A)+P(B)-1$? Can anyone show me to solve this kind of question? Thanks in advance.

$\endgroup$
5
$\begingroup$

Rearranging the equation we can get $$ P(A\cap B)=P(A)+P(B) - P(A\cup B) $$ Now it is clear that $P(A\cup B) \leq 1$ which allows you to conclude.

$\endgroup$
  • $\begingroup$ Yea I did this. But I didn't know that I could conclude after that. Thanks in advance! $\endgroup$ – Mathxx Jan 18 '17 at 9:36
2
$\begingroup$

Note that $\displaystyle\left(\bigcap_{i=1}^nA_i\right)^c=\bigcup_{i=1}^nA_i^c\quad$, by De Morgan's law.

Then, taking the probability function on both sides we have, $$P\left(\bigcap_{i=1}^nA_i\right)=1-P\left(\bigcup_{i=1}^nA_i^c\right)$$

Now, using Boole's inequality we have, $\displaystyle P\left(\bigcup_{i=1}^nA_i^c\right)\le\sum_{i=1}^nP\left(A_i^c\right)$

$\displaystyle\implies 1-P\left(\bigcup_{i=1}^nA_i^c\right)\ge1-\sum_{i=1}^nP\left(A_i^c\right)$

$\displaystyle\implies P\left(\bigcap_{i=1}^nA_i\right)\ge1-\sum_{i=1}^n\left(1-P\left(A_i\right)\right)=1-n+\sum_{i=1}^nP\left(A_i\right)$

i.e., $\displaystyle P\left(\bigcap_{i=1}^nA_i\right)\ge \sum_{i=1}^nP\left(A_i\right)-(n-1)$, which is Bonferroni's inequality.

For $n=2$, you have your required result.

$\endgroup$
1
$\begingroup$

Because $P(A\cup B) \leq 1$ (and $-P(A\cup B) \geq -1$ ), we get:

$P(A\cap B) = P (A)+P(B) - P(A\cup B) \geq P (A)+P(B) - 1$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.